Effect of different starter cultures on the sensory properties and microbiological quality of Atole agrio, a fermented maize product. (March 2020) - Väkeväinen, Kati; Hernández, Jessica; Simontaival, Anna-Inkeri; Severiano-Pérez, Patricia; Díaz-Ruiz, Gloria; von Wright, Atte; Wacher-Rodarte, Carmen; Plumed-Ferrer, Carme
Abstract: Maize is staple food in Central and Latin America, Southern and Eastern Africa, and fermentation processes are widely used to improve food safety and quality. Atole agrio is a typical Mexican fermented maize beverage, that, unlike many others, is made with a non-nixtamalized young maize. The aim of this research was to select endogenous lactic acid bacteria (LAB) starter cultures able to control atole agrio fermentation and preserve the sensory properties of spontaneously fermented atole agrio . Lactococcus lactis A1MS3 (12.6 ± 0.09 log cfu g −1 ) and Pediococcus pentosaceus S0l10 (11.7 ± 0.02 log cfu g −1 ), alone or as 1:1 v/v co-culture (12.5 ± 0.17 log cfu g −1 ) induced higher LAB counts than spontaneous fermentation (9.1 ± 0.11 log cfu −1 ) leading to fast acidification of the product. Starter cultures noticeably decreased Enterobacteriaceae, leading to microbiologically safer end product. Rapid sensory evaluation technique Flash profile (FP) differentiated the taste of products fermented with Lc. lactis alone or as co-culture with P. pentosaceus as sweet, tortilla and maize-like, compared to the acid and bitter taste of spontaneously fermented maize. We demonstrated the usability of FP in fermented maize products and showed, that atole agrio with enhanced sensory profile can be obtained by controlled fermentation. Highlights: Inoculation of starter cultures shortened atole agrio fermentation time. The taste of atole agrio was improved when starter cultures were used. Flash Profile differentiated of the sensory effects of starter cultures. Promising starter cultures for industrial applications were obtained.